The Russian - Coes, Ben (St. Martin's Press, 2019)
Ruthless, clever, and unbelievably violent, the Russian mafia has rapidly taken over the criminal underworld in the U.S. and law enforcement has been unable to stem the tide. When a powerful Russian mob family declares war by publicly executing two high-profile American politicians, the message is unmistakable <U+2013> opposition will be met with overwhelming deadly force. With no other viable options, the President creates a clandestine assassinations team to find and eliminate the unreachable men running this deadly criminal operation. The CIA recruits two Tier 1 operators <U+2013> former Navy SEALs Billy Cosgrove and Rob Tacoma. But before they can even get started, the Russians act <U+2013> murdering Cosgrove in his own home. Now Tacoma is on his own against an organization with endless resources and no boundaries. Step one requires the near impossible - find and kill the hidden mob boss behind Cosgrove<U+2019>s death. To do this, he<U+2019>ll have to take on an army in a battle where there are no rules and no limits.